The Lack of Effect of Botulinum Toxin-A on Upper Limb Activity in Chronic Stroke: A Short Report from the InTENSE Trial - Ian D. Cameron; Louise Ada; Maria Crotty; Mithu Palit; Lydia Huang; John Olver; Steven G. Faux; Senen Gonzales; Brian Anthonisz; Malcolm Bowman; Yuriko Watanabe; Yan Chow; et al. (Toxins)
We examined the effect of botulinum toxin-A on upper limb impairments and activity limitations in chronic stroke. This study is a secondary analysis of control group data from a national, multicenter, Phase III randomized trial with a masked outcome assessment. We studied 71 stroke survivors who received a botulinum toxin-A injection in any muscle(s) that crosses the wrist due to significant spasticity after a stroke greater than 3 months previously. We measured upper limb activity, spasticity, range of motion, grip strength, pain and other outcomes at injection and three months later. The median difference between injection and 3 months later was 0.0 blocks/s (interquartile range (IQR) 0.0) on the Box and Block Test, 0/4 (IQR 1) on the Tardieu Scale, 4 degrees (IQR 26) of wrist extension, 0.0 kg (IQR 2) of grip strength, 0.0 (IQR 1.5) on the 10 cm visual analogue scale for pain, 0/100 (IQR 21) on the 10 cm visual analogue scale for overall health, 0/3 (IQR 0) for self-care and −2 (IQR 8) for burden of care. In chronic stroke survivors who have little activity in their upper limb, botulinum toxin-A is not effective in improving any measured outcomes and does not appear to be clinically justified in this population with severe activity limitations.